Deep-water Ascidiacea from the Sea of Japan - Sanamyan, Karen; Sanamyan, Nadya (Zootaxa, 2012)
Four solitary ascidians are recorded in the deep-water material from the Sea of Japan. Two species, Agnezia orthenteronand Pelonaia bursaria are recorded for the first time since original descriptions, a third species, Styela squamosa, is awidely distributed deep-water species not known previously from the Sea of Japan. A fourth species was identified only to a genus level.